2011
DOI: 10.1016/j.vaccine.2011.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Development of DENVax: A chimeric dengue-2 PDK-53-based tetravalent vaccine for protection against dengue fever

Abstract: Dengue. virus infection is the leading arboviral cause of disease worldwide. A vaccine is being developed based on the attenuated DEN-2 virus, DEN-2 PDK-53. In this review, we summarize the characteristics of the parent DEN-2 PDK-53 strain as well as the chimeric viruses containing the prM and E genes of DEN-1, DEN-3 or DEN-4 virus in the genetic backbone of the DEN-2 PDK-53 virus (termed DENVax). Tetravalent DENVax formulations containing cloned, fully sequenced isolates of the DEN-2 PDK-53 virus and the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
93
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 41 publications
0
93
0
1
Order By: Relevance
“…Although immunocompromised, the A129 mouse strain retains an intact adaptive immune system and IFN-γ signaling pathway, thus enabling the study of antibody and T cell responses. The vaccine candidate, PDK53, was derived from the wild-type 16681 DENV2 strain through serial passage in primary dog kidney cells and is the principal component of the tetravalent DENVax vaccine currently under clinical development (30). The role of maternal PDK53-induced antibodies in disease enhancement was investigated in the context of a heterologous infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although immunocompromised, the A129 mouse strain retains an intact adaptive immune system and IFN-γ signaling pathway, thus enabling the study of antibody and T cell responses. The vaccine candidate, PDK53, was derived from the wild-type 16681 DENV2 strain through serial passage in primary dog kidney cells and is the principal component of the tetravalent DENVax vaccine currently under clinical development (30). The role of maternal PDK53-induced antibodies in disease enhancement was investigated in the context of a heterologous infection.…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge of this platform has been achieving sufficient attenuation for each monovalent component while preserving immunogenicity for all 4 serotypes. There are three LAV vaccine candidates under active clinical development (9)(10)(11). These vaccines are based on recombinant attenuated and chimeric viruses representing each of the four dengue serotypes.…”
mentioning
confidence: 99%
“…The protective efficacy of this tetravalent dengue vaccine in a phase 2b trial in Thailand was recently reported (13), and large-scale phase 3 trials are ongoing (14). Another chimeric dengue vaccine under clinical trial is developed based on the known attenuated DENV-2 strain PDK53 (6,10,15,16). Additionally, recombinant DENV-4 with a deletion of 30 nucleotides in the 3= UTR (DEN4⌬30) has been successfully utilized as a backbone for chimeric dengue vaccine development (11,(17)(18)(19)(20).…”
mentioning
confidence: 99%